2018
DOI: 10.29333/ejmste/91898
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Achievement in Basic Electronics: Effects of Scaffolding and Collaborative Instructional Approaches

Abstract: This study determined effects of scaffolding and collaborative instructional approaches on students' achievement in Basic Electronics. A quasi-experimental research design was adopted for the study. The performance of 105 Senior Secondary two (SS 2) students in Basic Electronics was obtained after being taught with scaffolding and collaborative instructional approaches using the Basic Electronics Cognitive Achievement Test (BECAT). Data collected were analyzed using mean and ANCOVA. Results revealed that a col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Nevertheless, some researchers found no gender differences or mostly a minor difference. A study by Atsumbe, Owodunni, Raymond, and Uduafemhe (2018), revealed that gender made no significant difference in students' educational achievement. The result of a study investigated by Ajogbeje and Alonge (2012) also shows no gender difference in junior secondary school mathematics achievement.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nevertheless, some researchers found no gender differences or mostly a minor difference. A study by Atsumbe, Owodunni, Raymond, and Uduafemhe (2018), revealed that gender made no significant difference in students' educational achievement. The result of a study investigated by Ajogbeje and Alonge (2012) also shows no gender difference in junior secondary school mathematics achievement.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, this current research is intended to examine how students' academic achievement in secondary school quantitative economics is affected by feedback, and or feedback with remediation. Furthermore, studies have equally indicated that gender influences student's academic achievement (Ajogbeje and Alonge, 2012;Amuda, Ali, Durkwa, 2016;Atsumbe et al, 2018;Dania, 2014). In this study, the possible effect of gender on students' achievement in quantitative economics was also determined.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Robinson (2017) reported that gender had no influence on the performance of students in basic electricity when taught using Computer Aided Instruction (CAI). Astumbe, Owodunna, Raymond and Uduafemhe [29] affirmed that there was no significant effect of gender on students' achievement in basic electricity using scaffolding and collaborative instructional approaches. Sex factor as an area of educational research has generated conflict and inconclusive findings; and its' disparities in male and female students' achievement and retention in science and technology subjects have not been settled.…”
Section: Introductionmentioning
confidence: 94%
“…Scaffolding is a supportive interaction by guiding and providing necessary resources to solve problems (Razaghi et al, 2019;Hermawati & Chen, 2023;Pitriyani & Fitriani, 2023). Scaffolding is considered a strategy that refers to solving problems or to improve the quality of their scientific arguments (Chotirat & Teosakul, 2017;Weng et al, 2017;Atsumbe et al, 2018;Yolviansyah & Hermanto, 2023). Scaffolding can help students fix problems, simplify complex tasks, or explain complex procedures (Park et al, 2020;Syarkowi et al, 2023;Wulandari & Jumadi, 2023).…”
Section: Introductionmentioning
confidence: 99%